The documentation of Aleppine' Ajami Rooms from the Ottoman period - Alafandi, Rami; Abdul Rahim, Asiah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
The objective of this paper is to document the polychrome wooden `ajami rooms. Aleppo is the second largest city in Syria (after the capital Damascus) and is the commercial capital of Syria. Aleppo has a long history, extending from the third millennium B.C to the Islamic era. Aleppo flourished and became a very important station on the Silk Road. Later, Aleppo became a part of the Ottoman Empire from 1516 to 1918, and the third largest city in the Ottoman Empire after Istanbul and Cairo. As part of this empire, local Aleppine architects and craftsmen combined their techniques and cultural heritage with Ottoman culture. This research employs a historical, photographic and descriptive approach to document the ‘ajami rooms by using mostly the photographs, that were taken by the first author in 2006. Since 2012 much of Syria’s architectural heritage has been destroyed due to internal war. In Aleppo, the losses in both the ancient and modern parts of the city have been tremendous including some traditional houses with ‘ajami. This paper will highlight some recommendations to protect the ajami rooms from the current conflict and restore it for future use.